PREVENTION OF PHLEBITIS: PREVENTIVE ACTIONS FOR PATIENT SAFETY - Santos da Silva, Victor (Health and Society, 2023)
Phlebitis is an inflammation of a vein, usually caused by an infection, trauma, or chemical irritation. Symptoms include pain, swelling, and redness at the site of the affected vein, as well as fever and chills in more severe cases.